Numder magic - Pinel, Adrian; Pinel, Jeni (London Red kite, 2011)
Mathematical Games is one of three titles in the Mad About Maths series. This is a bright, colourful series designed to help Key Stage 2 children (7-11's) develop their number skills and mathematical confidence, mainly by learning at home in support of their National Curriculum classsroom studies. Each book is packed with mathematical puzzles and games and includes 12 pages of press-out pieces to use with the activities (counters, board games, etc). The books are fun and stimulating and turn a subject which many children find slightly forbidding into something which is accessible and enjoyable. Generally speaking, the activities are designed for small groups as well as individuals and so encourage social as well as individual play
Games & Recreations
1
Keywords: Games